Determinants of Financial Performance of Islamic Banking in Indonesia: the Role of Zakat, CSR, and CEI - Janah, Anis Zahrotul; Muharrami, Rais Sani (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
This study examines the effect of zakat, Corporate Social Responsibility, and Corporate Ethical Identity on the financial performance of Islamic banking as proxied by Return on Asset (ROA). This research helps the Financial Services Authority (OJK) policy on the importance of implementing ethical values in Islamic banking. Previous studies have different results from each other, so this study expands the sample from previous studies. Quantitative research is used in this study. The data source of this study is the annual financial statements of ten Islamic Commercial Banks registered with OJK between 2019 and 2023. Literature and documentation studies were used to collect data. The analysis method used is panel data regression analysis method. The results showed that partially the disclosure of zakat has a significant effect on financial performance. While the disclosure of CSR and CEI has no significant effect on financial performance. CSR is measured using Islamic Social Reporting (ISR) and CEI is measured using Ethical Identity Index (EII). In addition, simultaneously Zakat, CSR, and CEI affect financial performance. The findings of this study provide important implications and contributions as a reference for regulators, Islamic bank management, and other stakeholders in developing policies and strategies aimed at strengthening ethical identity and increasing transparency in the disclosure of zakat and CSR. This has led to an increase in stakeholder confidence and the financial performance of Islamic banking in Indonesia.